Cadmium Tolerance and Detoxification Mechanisms of Lentinula edodes: Physiology, Subcellular Distribution, and Chemical Forms - Gaigai Chen; Bowen Han; Wene Nan; Xiaobo Dong (Microorganisms)
Lentinula edodes has a strong cadmium-enrichment ability, posing a potential threat to human health. However, the cadmium tolerance and detoxification mechanisms of Lentinula edodes are not understood. We investigated the physiological responses, subcellular distribution, and chemical forms of cadmium in two Lentinula edodes strains (1504 and L130) with contrasting cadmium tolerance. The results showed that appropriate, low-level cadmium promoted mycelial growth, and higher cadmium exposure induced obvious inhibition of mycelial growth by damaging the cell wall and membrane structure and triggering the overproduction of ROS. Antioxidant enzymes played an important role in cadmium detoxification, as well as functional group modulation. Cadmium was predominantly distributed in the cell wall fraction, and NaCl-extractable cadmium was the main chemical form. Enhanced antioxidant enzyme activities, reduced cadmium accumulation, and increased HAc-extractable cadmium with less toxicity promoted stronger cadmium tolerance and detoxification abilities in L130 compared to 1504. Thus, this study provides new insights into cadmium tolerance and detoxification in Lentinula edodes.